2015
DOI: 10.1016/j.bjorl.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vibrotactile vestibular substitution on vestibular rehabilitation – preliminary study

Abstract: The present findings show that sensory substitution using the vibrotactile stimulus of the Vertiguard™ system helped with the integration of neural networks involved in maintaining posture, improving the strategies used in the recovery of body balance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 24 publications
2
43
0
1
Order By: Relevance
“…Our results identified only three patients with a MDC (42.85%). Brugnera et al (2015) , demonstrated different results using a mechanical approach in which patients improved in physical and functional DHI. However, the emotional dimension of the test showed no difference.…”
Section: Discussionmentioning
confidence: 99%
“…Our results identified only three patients with a MDC (42.85%). Brugnera et al (2015) , demonstrated different results using a mechanical approach in which patients improved in physical and functional DHI. However, the emotional dimension of the test showed no difference.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that body sway reductions can be retained for hours to days following short-term (i.e., less than one week) balance training with SA [17,18,56]. Other studies have investigated changes in body sway or clinical outcomes following multi-session (i.e., more than 1 week) training with SA [9,10,14,51]. For example, Basta et al reported reduced body sway and improved clinical outcome measures (e.g., Sensory Organization Test (SOT) and Dizziness Handicap Inventory (DHI)) in people with vestibular disorders who trained with vibrotactile SA over a two-week (i.e., ten-session) training program, but observed no such effect in their placebo group training with a sham device which generated random SA cues [10].…”
Section: Introductionmentioning
confidence: 99%
“…Vibrotactile feedback systems have been used as physical non-interrupting interfaces for movement training [1719] since they are generally considered to be effective, small and economical. Vibrotactile feedback systems have applications in posture and gait training for individuals with age-related balance declines [20], individuals with vestibular [21] and neurological disorders [22] and knee osteoarthritis [23] and various rehabilitation applications as it is effective, small and economical [16]. A TactaPack wearable vibrotactors system has shown potential to reduce injuries during therapy due to improper patient joint movements [24].…”
Section: Introductionmentioning
confidence: 99%